2010
DOI: 10.4049/jimmunol.0903480
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Activates Microglia by Inducing the Expressions of Matrix Metalloproteinases and the Subsequent Activation of Protease-Activated Receptor-1

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
194
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(197 citation statements)
references
References 42 publications
(51 reference statements)
2
194
0
1
Order By: Relevance
“…Indeed, we have observed a strong innate immune response in primary glial and microglial cell cultures elicited by exogenous, non-aggregated Syn (Roodveldt et al, 2010). Interestingly, a comparative study using unmodified aSyn has recently shown that exogenous non-aggregated Syn induces higher TNF-, IL-1 and ROS release levels than aggregated Syn in microglia (Lee et al, 2010). These and other recent findings point at the importance of exploring the effects on the immune response of aggregated as well as non-aggregated Syn.…”
Section: Syn-induced Microglial Activationmentioning
confidence: 91%
“…Indeed, we have observed a strong innate immune response in primary glial and microglial cell cultures elicited by exogenous, non-aggregated Syn (Roodveldt et al, 2010). Interestingly, a comparative study using unmodified aSyn has recently shown that exogenous non-aggregated Syn induces higher TNF-, IL-1 and ROS release levels than aggregated Syn in microglia (Lee et al, 2010). These and other recent findings point at the importance of exploring the effects on the immune response of aggregated as well as non-aggregated Syn.…”
Section: Syn-induced Microglial Activationmentioning
confidence: 91%
“…In addition to studies of its release and uptake, extracellular α-syn has been reported to have effects on neurotoxicity 15,19,20 and inflammation. 14,18,[21][22][23][24] Recent observations that the transplants grafted into the brain of PD patients displayed Lewy bodies 25,26 were considered to be connected with Braak et al's proposal that Lewy body pathology spreads from one brain area to another according to a stereotypic pattern in specific stages. 27 Consequently, more recent in vitro and in vivo experiments [28][29][30][31][32][33] have shown that α-syn aggregates released from neuronal cells can be transferred to neighboring neurons and form Lewy body-like inclusions, providing a mechanistic basis for the spread of α-syn pathology in PD patients and a hypothesis that a prion-like mechanism may underlie the progression of PD.…”
Section: Proteolytic Clearance As a Therapeutic Approach Against Pd Amentioning
confidence: 99%
“…62 Alterations of MMPs have also been observed in neurodegenerative diseases other than PD, 79 and extracellular α-syn has been reported to regulate the activity of MMPs. 22,80,81 Although the association between the plasmin system in the CNS and PD has yet to be established, the reduction of tPA activity by extracellular α-syn in primary astrocytes and microglia has been reported. 80 Extracellular α-syn has also been shown to increase PAI-1 expression in neurons, astrocytes and microglia and thus may inhibit plasmin activity, 59 suggesting that the plasmin system may be dysregulated in PD.…”
Section: The Relationship Between Pd and α-Synmentioning
confidence: 99%
“…For example, striatal implantation of PAR1 AP induced brain inflammation and neurobehavioral deficits in mice (Boven et al, 2003). Recent evidence has also pointed to a role for PAR1 in the pathogenesis of Parkinson's disease which is characterized by gliosis, reduced dopamine expression and damage to the neuronal nigrostriatal pathway (Lee et al, 2010). Using inhibitors of PAR1 and PAR1 APs these authors showed that α-synuclein, a neuronal protein associated with Parkinson's disease, upregulates MMPs which then act through PAR1 to increase expression of IL1-β and TNF-α as well as NO and other reactive oxygen species (Lee et al, 2010).…”
Section: Nervous Systemmentioning
confidence: 99%
“…Recent evidence has also pointed to a role for PAR1 in the pathogenesis of Parkinson's disease which is characterized by gliosis, reduced dopamine expression and damage to the neuronal nigrostriatal pathway (Lee et al, 2010). Using inhibitors of PAR1 and PAR1 APs these authors showed that α-synuclein, a neuronal protein associated with Parkinson's disease, upregulates MMPs which then act through PAR1 to increase expression of IL1-β and TNF-α as well as NO and other reactive oxygen species (Lee et al, 2010). In addition, in a murine chemical model of Parkinson's disease that uses the neurotoxic agent, 1-methyl-4-phenyl-1,2,3,6-tetrahydro-pyridine (MPTP) to cause disease, PAR1-deficient mice are protected, with elevated levels of dopamine and reduced microgliosis compared with wild-type mice .…”
Section: Nervous Systemmentioning
confidence: 99%